Bacteriological examination of the udder samples collected from sheep and goats slaughtered at a local abattoir in elazığ - H. Basri Gülcü; Hasan Öngör (Eurasian Journal of Veterinary Sciences)
In this study. 133 udder lobes from 89 mastitic sheep and 67 from 40 mastitic goats slaughtered at a local abattoir in Elazığ, were collected for bacteriological examination. The agenis isolated and identified from the udder lobes of the sheep were Staphylococcus aureus (24.06%). Escherichia coli (10.53%), Actinomyces pyogenes (7,52%). Streptococcus uberis (7.52%), Streptococcus dysgalactiae (6.01%), Streptococcus agalactiae (5.26%), Staphylococcus epıdermidis (3.76 %) and Mannheimia haemolytica (3.76 %). The agents isolated and identified from the udder lobes of the goats were Staphylococcus aureus (25,37%), Escherichia coli (8.96%), Staphylococcus epıdermıdis (7.46 %). Streptococcus agalactiae (7.46%), Actinomyces pyogenes (7.46%), Streptococcus dysgalactiae (5,97%), Streptococcus ubens (2.99%) and Mannheimia haemolytica (2.99 %)